Challenges to using metal structures in the design of school buildings in hard-to-reach areas of Russia - Osipova Sofia V.; Konovalova Elena A. (Архитектон)
The article analyzes the need for major repairs and construction of new schools in Russia, especially in northern and hard-to-reach regions. Space planning and engineering design principles for school design are defined. The purpose of the article is to provide arguments supporting the choice of metal frames and light thin-walled steel structures as a priority in the design and construction of schools. International and domestic experiences in school construction using steel frames are considered. Examples from Russian suppliers of structural steel are provided.